1996
DOI: 10.1046/j.1365-2141.1996.d01-1896.x
|View full text |Cite
|
Sign up to set email alerts
|

DELETIONS OF CHROMOSOME 20q AND THE PATHOGENESIS OF MYELOPROLIFERATIVE DISORDERS

Abstract: Myeloproliferative disorders (MPD) and myelodysplastic syndromes (MDS) represent an overlapping spectrum of clonal preleukaemic conditions in which mutations have resulted in dysregulation of multipotent haemopoietic progenitors. An interstitial deletion of the long arm of chromosome 20 is a recurring abnormality associated with both of these classes of disorders. The association of 20q deletions with 'stem cell' disorders suggests that the deletion may mark the site of one or more genes, loss or inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 0 publications
0
32
1
3
Order By: Relevance
“…This is consistent with the frequent deletions on chromosome 20q observed in cytogenetic studies of MDS. 20 The FAL was calculated as the ratio of chromosomal arms…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the frequent deletions on chromosome 20q observed in cytogenetic studies of MDS. 20 The FAL was calculated as the ratio of chromosomal arms…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified deletions at chromosome 1q21-22 in cancers of the breast, 24 colon, 10 lung, 12 and stomach. 20 Also, LOH has been reported at 1q23-32 in breast cancer. 25 Translocation between 1q and 5q, 26 trisomy 1q, 27 and either rearrangement or duplication of chromosome 1q 28 have been observed in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…In MDS, isolated 20q deletions were found to be prognostically favorable [27][28][29], whereas in the MPN an impact on prognosis so far was not determined [35].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myeloid malignancies are associated with deletions of 20q (10)(11)(12). The 20q minimal deleted region spans 1.9 Mb and contains multiple genes, including L3MBTL1 (13), a transcriptional repressor (14)(15)(16) homologous to the Drosophila tumor-suppressor gene lethal(3) malignant brain tumor (17,18).…”
Section: Introductionmentioning
confidence: 99%